2022
DOI: 10.1002/ppul.26066
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound to evaluate lung recruitment in neonates with respiratory distress (RELUS study)

Abstract: Background: Lung ultrasound (LUS) is a bedside tool useful to diagnose neonatal respiratory disease and to guide surfactant therapy. LUS scores have emerged as useful tool for newborn respiratory distress but is unknown if respiratory support settings may influence it. The aim of the study was to evaluate the feasibility of LUS scores evaluating lung recruitment in term newborns with respiratory distress when noninvasive respiratory it is increased.Material and Methods: Prospective study in a tertiary neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Previous reports have shown that B lines on LUS correlate with the presence of lung water content 20,32 . Although controversial reports have found the efficacy of the LUS score in the diagnosis of lung pathologies, use in the neonatal intensive care unit (NICU), is increasing 33–35 . Only a few studies have evaluated the effects of PDA in preterm using LUS 6,10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that B lines on LUS correlate with the presence of lung water content 20,32 . Although controversial reports have found the efficacy of the LUS score in the diagnosis of lung pathologies, use in the neonatal intensive care unit (NICU), is increasing 33–35 . Only a few studies have evaluated the effects of PDA in preterm using LUS 6,10 .…”
Section: Discussionmentioning
confidence: 99%
“…20,32 Although controversial reports have found the efficacy of the LUS score in the diagnosis of lung pathologies, use in the neonatal intensive care unit (NICU), is increasing. [33][34][35] Only a few studies have evaluated the effects of PDA in preterm using LUS. In this study, we planned an "early symptomatic" policy for the F I G U R E 3 ROC curve for assessing for patent ductus arteriosus for closure therapy with lung ultrasound score.…”
Section: Correlation Analysismentioning
confidence: 99%
“…LUS-guided recruitment better mitigated lung inflammation and reduced duration of mechanical ventilation. LUS guided recruitment has been attempted on non-invasive ventilation as well [ 60 ]. LUS guided recruitment constitutes an act of integrated CPUS, as the assessment of the hemodynamic status and eventual stabilization are prerequisite for the success of LUS guided open lung ventilation.…”
Section: Cardiopulmonary Ultrasoundmentioning
confidence: 99%
“…There were intriguing studies using LU for predicting a level of respirator support or for evaluating clinical efficacy. Rodriquez‐Fanjul et al 5 conducted a prospective study with 40 full‐term neonates who required nCPAP within first 6 h of life with an LUS higher than 8. They found that LUS was no different between the first LU, which was done in patients on nasal CPAP (nCPAP) (6 cmH 2 O), and the second LU, which was done after the subjects were placed on duo positive airway pressure (12/6 cmH 2 O).…”
Section: Progress In Neonatal Lung Ultrasound (Lu)mentioning
confidence: 99%
“…Study outcome [1] Nationwide prospective cross-sectional survey LU in diagnosis of respiratory diseases: PTX (95%), RDS (89%), TTN (89%), PE (88%), Atelectasis (66%), Pneumonia (64%), BPD (43%), CPAM (41%), CDH (34%) [2] Review of literature LU patterns: type 1 (white lung), type 2 (prevalence of B lines), type 3 (predominance of A lines) LUS: 0: A-pattern (presence of only A-lines), 1: B-pattern (presence of 3 or more B-lines), 2: severe B-pattern (presence of crowded and coalescent B lines), 3: extended consolidation [3] Cross-sectional study Comparing POCUS to standard-of-care for ETT placement: POCUS was rapid and reliable [4] Retrospective cohort study Diagnosis of PTX: A-line in the anterior transverse plan was superior to mirrored ribs sign [5] Prospective study Evaluating lung recruitment: There was no difference in LUS between the first LU (LU-1) and LU-2, but there was an improvement in the oxygenation, RR, and CO 2 between LU-1 and LU-3.…”
Section: Reference Study Typementioning
confidence: 99%